Improving the Efficiency of Budgeting in Industrial Enterprise: The case of Russia, Italy, and the Middle East - Amjed Hameed Majeed; Raffaele Fiume; Nikolay Kuznetsov; Margarita Vasyunina; Alexander Semin; Mikhail Kosov (Emerging Science Journal, 2023)
The study improved budgeting efficiency at industrial enterprises with evidence from Russia, Italy, and the Middle East. In the era of contemporary globalization and technological advancement, a budgeting system holds paramount significance in the effective management of the financial operations and activities, enhancing the overall efficiency of the firm's cash management, mitigating the risk of finance misallocation, and improving the overall financial performance of the enterprise. However, despite its effectiveness, there is a lack of evidence supporting budgeting automation and its efficiency in managing industrial enterprises. More so, limited theoretical and practical relevance is found in the context of Russia, Italy, and the Middle East. This research intended to fill the existing research gap where a qualitative research design was opted. Primary data were collected from the budgeting heads of 3 pharmaceutical firms, each located in Russia, Italy, and Iran. In-depth interviews with 3 budgeting heads identified that the conventional incremental budgeting system needed amendment and replacement with a consolidated and contemporary yet flexible approach to bring radical improvements at the macro-environment level within the industrial enterprise. The key findings led to the development of a model to improve budgeting efficiency, comprising three components: information and analytical/accounting support for budgeting, production accounting information, and a combination of the regulated operation prices. The consolidation of these three components can yield budgeting efficiency. Doi: 10.28991/ESJ-2023-07-01-013 Full Text: PDF